The Prognostic and Clinicopathological Significance of IGF-1R in NSCLC: a Meta-Analysis - Jun Zhao (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Accumulating studies have reported that IGF-1R (Insulin-like growth factor-1 receptor) is aberrantly expressed in NSCLC (non-small cell lung cancer), but the role of IGF-1R in NSCLC remains controversial. The present paper assessed the precise role of IGF-1R in NSCLC. Methods: We comprehensively searched PubMed, EMBASE, and Web of Science in March 2017. Combined HRs and ORs were used to evaluate the prognostic and clinicopathological significance of IGF-1R in NSCLC respectively. Results: A total of 10 eligible studies including 8 on overall survival, and 10 on clinicopathological features were identified from the databases. The results showed that high expression of IGF-1R was associated with shorter OS (overall survival) of NSCLC patients (pooled HR 1.17,95 % CI 1.00–1.36). In addition, we found that IGF-1R was related to smoking status (OR=1.82, 95 % CI=1.35-2.44) and IGF-1R tended to be highly expressed in SCC (squamous cell carcinoma) (OR=3.40 95 % CI: 1.95-5.95). Conclusions: In summary, this meta-analysis revealed that high expression of IGF-1R was associated with poor prognosis in NSCLC.